Banana Genome Hub: empowering global collaboration in research - Rouard, Mathieu (2024)
Over ten years of service, the Banana Genome Hub has earned recognition in peer-reviewed journals and draws thousands of scientists globally each year, particularly from the Global South. As an important information system in the landscape of plant genomic research, it has supported numerous organizations worldwide to conduct studies on banana genome evolution and diversity. This understanding is key to conserving genetic resources and ensuring the sustainability of banana crops worldwide.